Controlled Polymerisation of Arylacetylenes with Well-Defined Rhodium Catalysts - Tan, Nicholas Sheng Loong (Curtin University, 2020)
This thesis details the synthesis of six new rhodium(I)-vinyl and -aryl complexes and their extensive characterisation using a suite of spectroscopic techniques with a primary emphasis on the evaluation of these complexes as initiators for the stereospecific (controlled) (co)polymerisation of phenylacetylenes and other substituted arylacetylene substrates.